Effect of the L-D1 alleles on leaf morphology, canopy structure and photosynthetic productivity in upland cotton (Gossypium hirsutum L.) - Hui JIANG; Ming-wei GAO; Ying CHEN; Chao ZHANG; Jia-bao WANG; Qi-chao CHAI; Yong-cui WANG; Jin-xiu ZHENG; Xiu-li WANG; Jun-sheng ZHAO (Journal of Integrative Agriculture, 2023)
One of the most important objectives for breeders is to develop high-yield cultivars. The increase in crop yield has met with bottlenecks after the first green revolution, and more recent efforts have been focusing on achieving high photosynthetic efficiency traits in order to enhance the yield. Leaf shape is a significant agronomic trait of upland cotton that affects plant and canopy architecture, yield, and other production attributes. The major leaf shape types, including normal, sub-okra, okra, and super-okra, with varying levels of lobe severity, are controlled by a multiple allelic series of the D-genome locus L-D1. To analyze the effects of L-D1 alleles on leaf morphology, photosynthetic related traits and yield of cotton, two sets of near isogenic lines (NILs) with different alleles were constructed in Lumianyan 22 (LMY22) and Lumianyan 28 (LMY28) backgrounds. The analysis of morphological parameters and the results of virus-induced gene silencing (VIGS) showed that the regulation of leaf shape by L-D1 alleles was similar to a gene-dosage effect. Compared with the normal leaf, deeper lobes of the sub-okra leaf improved plant canopy structure by decreasing the leaf area index (LAI) and increasing the light transmittance rate (LTR), and the mid-range LAI of sub-okra leaf also guaranteed the accumulation of cotton biomass. Although the chlorophyll content (SPAD) of sub-okra leaf was lower than those of the other two leaf shapes, the net photosynthetic rate (Pn) of sub-okra leaf was higher than those of okra leaf and normal leaf at most stages. Thus, the improvements in canopy structure, as well as photosynthetic and physiological characteristics, contributed to optimizing the light environment, thereby increasing the total biomass and yield in the lines with a sub-okra leaf shape. Our results suggest that the sub-okra leaf may have practical application in cultivating varieties, and could enhance sustainable and profitable cotton production.